Accidental Nasal Myiasis Caused by Megaselia rufipes (Diptera: Phoridae) in a Child. Issue 1 (9th September 2020) - Giangaspero, A; Barlaam, A; Pane, S; Marchili, M R; Onetti Muda, A; Putignani, L; Hall, M J R
Abstract: A case of a nasal myiasis in a 3-yr-old Italian girl who was referred to Bambino Gesù Hospital in Rome, Italy, is reported. Larvae discharged with the nasal mucus were microscopically identified as Megaselia spp.; DNA barcoding analysis showed that they belonged to the 'scuttle fly' species Megaselia rufipes (Meigen). Based on the patient's history, she became infected when she played outside. This is the first report of myiasis in humans due to M. rufipes (Diptera: Phoridae).